2015
DOI: 10.1002/anie.201502438
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Nanostructured Ni5P4 Films and their Use as a Non‐Noble Bifunctional Electrocatalyst for Full Water Splitting

Abstract: The investigation of nickel phosphide (Ni5 P4 ) as a catalyst for the hydrogen (HER) and oxygen evolution reaction (OER) in strong acidic and alkaline environment is described. The catalyst can be grown in a 3D hierarchical structure directly on a nickel substrate, thus making it an ideal candidate for practical water splitting devices. The activity of the catalyst towards the HER, together with its high stability especially in acidic solution, makes it one of the best non-noble materials described to date. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
439
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 798 publications
(481 citation statements)
references
References 48 publications
31
439
1
4
Order By: Relevance
“…However Schaak et al achieved a contradicting result and reported on quickly degraded Ni 2 P to Ni when used as a HER electrocatalyst in 1 M KOH [53] . A comparable HER/OER activity and very good stability under catalysis conditions in 1 M KOH was reported for Ni 5 P 4 NPs (HER: η= 150 mV at 10 mA/cm 2 ; OER: η= 330 mV at 10 mA/cm 2 ) [54] . Table S4 gives an idea of the overall electrocatalytic OER-and HER properties of recently developed bifunctional electrocatalysts.…”
Section: Her Properties In Acidic/alkaline Mediumsupporting
confidence: 62%
See 2 more Smart Citations
“…However Schaak et al achieved a contradicting result and reported on quickly degraded Ni 2 P to Ni when used as a HER electrocatalyst in 1 M KOH [53] . A comparable HER/OER activity and very good stability under catalysis conditions in 1 M KOH was reported for Ni 5 P 4 NPs (HER: η= 150 mV at 10 mA/cm 2 ; OER: η= 330 mV at 10 mA/cm 2 ) [54] . Table S4 gives an idea of the overall electrocatalytic OER-and HER properties of recently developed bifunctional electrocatalysts.…”
Section: Her Properties In Acidic/alkaline Mediumsupporting
confidence: 62%
“…al. [54] published data on Ni 2 P nanoparticles (NPs) respectively Ni 5 P 4 NPs as Janus catalyst in alkaline regime. Besides the already mentioned HER properties under acidic conditions [53] relatively high OER activity (290 mV overpotential) and high HER activity (~ 200 mV overpotential) combined with sufficient stability under catalysis conditions could be attested to Ni 2 P NPs in 1 M KOH at 10 mA/cm 2 as well [113] .…”
Section: Her Properties In Acidic/alkaline Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster III-4 focuses on Ni 2 P, which has high catalytic activity in HER and OER [75]. Notably, Ni 5 P 4 is stable, even under strongly acidic conditions (1M H 2 SO 4 ), and exhibits high catalytic activity despite that it does not contain a noble metal [76,77]. In addition, CoP has also been reported as an acid-stable catalyst for HER and OER [62].…”
Section: Emerging Technologies In Cluster IIImentioning
confidence: 99%
“…And the great demand of H 2 production triggers a body of research inputs on the water splitting, in which the key fact depends on the innovative exploitation regarding the design of efficient electrocatalysts helping lower the overpotential meanwhile obtaining decent reaction rates [5,6]. However, the most efficient noble-metal based electrocatalysts suffer from natural resource scarcity and high-cost, which hampers their broad utilization [7][8][9][10]. Although a variety of non-noble metal-based nanostructured materials such as Mo 2 C/MoO 2 [11], Co 9 S 8 /graphene [12], CoPS [13], CoMoS [14], NiMoN [15] have been reported, the facts are still far from satisfactory since these materials are either for oxygen evolution reaction (OER) catalysts working in strongly alkaline conditions or for hydrogen evolution reaction (HER) catalysts operating in strongly acidic mediums due to the thermodynamic convenience [5,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%